Analisis Perbandingan Preferensi Nasabah dalam Memilih Bank Syariah dan Bank Konvensional - Agni Andriani; Devina Febrianti Mulyana; Rianisa Yusrihaniz Altydar; Sitoh Sitoh; Muhammad Rindu Fajar (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This research aims to explore people's preferences in choosing between conventional and Islamic banks, focusing on the factors that influence customer decisions. The research method uses a descriptive qualitative approach by collecting primary data through Google Form questionnaires and secondary data through literature studies. The results show that although 80% of respondents understand the differences between conventional and Islamic banks, 83% still choose conventional banks. The main reasons include ease of infrastructure access, wider ATM availability, and integration with educational institutions and workplaces. Interestingly, 63% of respondents cite religion as a key consideration, and 70% consider the usury aspect of bank selection.Islamic banks are considered to have the advantage of applying the principles of fairness, transparency, and avoiding usury. However, obstacles such as limited ATM networks and lack of cooperation with companies are the main challenges in attracting customers.The study suggests Islamic banks to expand their networks, improve public education, and develop more innovative financial products that still comply with sharia principles.